Nigerian Labour Policy And Its Impact On The Railway Workers In Kaduna State 1960-1990s - Jackson, Andrew Buyengum (2023)
The study analyzed the development and impact of Nigeria’s labour and wage bargaining policies and how the railway transformed Kaduna state. It additionally investigated the impact of the collapse of NRC on the welfare of its workers in Kaduna from 1960 to the 1990s.